Screening for Pompe Disease in High-Risk Pediatric Patients: Experience from a Tertiary Care Center in Rajasthan - Nagpal, Tuhina; Goyal, Manisha; Mathur, Priyanshu; Agrawal, Kamlesh Kumar; Gupta, Ashok (Journal of Pediatric Neurology, 2023)
A high index of suspicion is required to diagnose rare genetic disorders, such as Pompe disease, with common clinical manifestations in children. There is a need to sensitize physicians regarding cues to early screening and diagnosis of such patients. Minimal epidemiological data are available on Pompe disease in India. The aim of this study was to determine the prevalence of Pompe disease in high-risk pediatric populations and determine the appropriateness of screening dried blood spot (DBS) tests to facilitate the diagnosis of Pompe disease. We screened pediatric patients presented with (1) unexplained hypotonia, respiratory distress, cardiomyopathy, and elevated liver function tests; and (2) unexplained limb girdle muscle weakness through a DBS test for enzyme assay. Those patients found positive underwent acid alpha-glucosidase mutational analysis. This prospective cross-sectional study was conducted in 45 suspected patients after approval from the institutional ethical committee. Of the 45 suspected patients, 9 (20%) were found to be positive by DBS test. Out of these nine tested, four (44.4%) were positive, two (22.2%) were negative, and three (33.3%) could not be tested for mutation analysis. The prevalence of genetically confirmed Pompe disease in high-risk populations was 8.8%. The results of this study show that clinical suspicion and DBS filter paper test facilitate early diagnosis and management, thereby improving the quality of life in patients. DBS test acts as a robust, rapid first-tier screening test for Pompe disease.
Keywords: Pompe disease; alpha-glucosidase; hypotonia; cardiomyopathy; dried blood spot test